Postpartum depression in Cambodia women - Tep, Pharin (ĐHGD, 2017)
The study explored the rate of postpartum depression and anxiety in women in Cambodia. According to GAD - 7 measures, 26% of the participants had moderate and severe anxiety. According to EPDS, 30% of the participants had moderate and severe depression. Therefore, policy makers, researchers, health practitioners should pay more attention to the issues in order to improve the life of women and their infants.